Characterization of focal cortical dysplasia with balloon cells by layer‐specific markers: Evidence for differential vulnerability of interneurons. (16th February 2017) - Nakagawa, Julia M.; Donkels, Catharina; Fauser, Susanne; Schulze‐Bonhage, Andreas; Prinz, Marco; Zentner, Josef; Haas, Carola A.
Summary: Objective: Focal cortical dysplasia (FCD) is a major cause of pharmacoresistant focal epilepsy. Little is known about the pathomechanisms underlying the characteristic cytoarchitectural abnormalities associated with FCD. In the present study, a broad panel of markers identifying layer‐specific neuron subpopulations was applied to characterize dyslamination and structural alterations in FCD with balloon cells (FCD 2b). Methods: Pan‐neuronal neuronal nuclei (NeuN) and layer‐specific protein expression (Reelin, Calbindin, Calretinin, SMI32 (nonphosphorylated neurofilament H), Parvalbumin, transducin‐like enhancer protein 4 (TLE4), and Vimentin) was studied by immunohistochemistry on paraffin sections of FCD2b cases (n = 22) and was compared to two control groups with (n = 7) or without epilepsy (n = 4 postmortem cases). Total and layer‐specific neuron densities were systematically quantified by cell counting considering age at surgery and brain region. Results: We show that in FCD2b total neuron densities across all six cortical layers were not significantly different from controls. In addition, we present evidence that a basic laminar arrangement of layer‐specific neuron subtypes was preserved despite the severe disturbance of cortical structure. SMI32‐positive pyramidal neurons showed no significant difference in total numbers, but a reduction in layers III and V. The densities of supragranular Calbindin‐ and Calretinin‐positive interneurons in layers II and III were not different from controls, whereas Parvalbumin‐expressing interneurons, primarily located in layer IV, were significantly reduced in numbers when compared to control cases without epilepsy. In layer VI, the density of TLE4‐positive projection neurons was significantly increased. Altogether, these data show that changes in cellular composition mainly affect deep cortical layers in FCD2b. Significance: The application of a broad panel of markers defining layer‐specific neuronal subpopulations revealed that in FCD2b neuronal diversity and a basic laminar arrangement are maintained despite the severe disturbance of cytoarchitecture. Moreover, it showed that Parvalbumin‐positive, inhibitory interneurons are highly vulnerable in contrast to other interneuron subtypes, possibly related to the epileptic condition.